If on a winter's night a traveler - Calvino, Italo (Everyman's library, 1993)
Based on a analogy between the reader's desire to finish the story and the lover's desire to consummate his or her passion, this book is the tale of two bemused readers whose attempts to reach the end of the same book are constantly and comically frustrate.